Desarrollo de un módulo de control de velocidad de motores de inducción jaula de ardilla, mediante variador de frecuencia y visualización en HMI, para el laboratorio de control industrial de la Universidad Técnica de Cotopaxi. - Araque Sigcha, Jorge Fabián (2020)
The analysis of process control systems today is of great interest due to its criticality and wide use in the work environment, of which perhaps the tuning is the process that demands more effort due to the complexity that results in order to obtain the adequate stabilization of the systems. That is why the purpose of this project is the development of a speed control module for squirrel cage induction motors for the Industrial Control Laboratory of the Electromechanical Engineering Career, which provides students with the ability to determine control and automation techniques to stabilize the speed of the motor under different loads. The module consists of a Siemens PLC S7-1200 as a central element, which through RS-485 communication, interacts with a Micro-master MM440 frequency converter to control the motor according to the speed requirements. Several controls have been developed to test its operation, and some tuning methods are applied to observe its operation and applicability. It is essential to point out that the system's mathematical model has been obtained so that the respective analysis can be carried out using simulation software in the future like the KTP400 HMI screen; the process can be adequately controlled, with options for displaying behavior curves in both open and closed loops. From the tests carried out, the appropriate parameters are determined to stabilize the process adequately.